IMPLEMENTASI METODE MONTESSORI UNTUK MENGEMBANGKAN KEMANDIRIAN ANAK DI RA MIFTAHUL ULUM MANGGISAN JEMBER - Khulusinniyah Khulusinniyah; Zahrotul Masrurah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Independence is an important thing that must be developed in children. If the child does not have the aspect of independence, it will grow into a home service generation; children who will always ask to be served and weak in facing life's challenges. They will find it difficult to adapt and solve various problems of life, so if this is allowed then they will grow into a weak generation, not a quality generation. Adopting from the Montessori curriculum, PTK is carried out at RA Miftahul Ulum to increase children's independence, by emphasizing practical skills that should be mastered by children. The results obtained indicate that the Montessori method can increase the independence of children, with the achievement of the percentage of independence of 87.5% above the 80% completeness target set.